Eradication of HIV by Transplantation of CCR5-Deficient Hematopoietic Stem Cells - Gero Hütter; Susanne Ganepola (The Scientific World Journal)
Today, 30 years after the onset of the HIV pandemic, although treatment strategies have considerably improved, there is still no cure for the disease. Recently, we described a successful hematopoietic stem cell transplantation in an HIV-1–infected patient, transferring donor-derived cells with a natural resistance against HIV infection. These hematopoietic stem cells engrafted, proliferated, and differentiated into mature myeloid and lymphoid cells. To date, the patient has not required any antiretroviral treatment, more than 4 years after allogeneic transplantation. In the analysis of peripheral blood cells and different tissue samples, including gut, liver, and brain, no viral load or proviral DNA could be detected. Our report raises the hope for further targeted treatment strategies against HIV and represents a successful personalized treatment with allogeneic stem cells carrying a beneficial gene. However, this case has ignited a controversy regarding the question of whether this patient has achieved complete eradication of HIV or not. Here we give an update on open questions, unsolved aspects, and clinical consequences concerning this unique case.